2019
DOI: 10.1063/1.5128937
|View full text |Cite
|
Sign up to set email alerts
|

A portable rotating disc as blood rheometer

Abstract: Abnormalities in biophysical properties of blood are often strong indicators of life threatening infections. However, there is no existing device that integrates the sensing of blood hematocrit (or equivalently, packed cell volume), viscosity, and erythrocyte sedimentation rate (ESR) in a unified paradigm for point-of-care diagnostics. In an effort to develop a rapid, integrated, accurate, portable, and inexpensive sensing platform to diagnose the corresponding pathophysical parameters, we develop a simple and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Behaving as Newtonian fluids at large shear rates and differing mainly at low shear rates, differences between the rheological models are expected for local shear rates below the order of 100 s −1 . A direct comparison of the contributions of the different models is displayed in terms of I L and I g , Equation (5), and shown in Figure 2a,b. The space averaging of the normalized viscosity (I L ) and the non-Newtonian importance factor enables the assessment of the temporal variations of the rheological models during the cardiac cycle.…”
Section: Viscosity Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaving as Newtonian fluids at large shear rates and differing mainly at low shear rates, differences between the rheological models are expected for local shear rates below the order of 100 s −1 . A direct comparison of the contributions of the different models is displayed in terms of I L and I g , Equation (5), and shown in Figure 2a,b. The space averaging of the normalized viscosity (I L ) and the non-Newtonian importance factor enables the assessment of the temporal variations of the rheological models during the cardiac cycle.…”
Section: Viscosity Coefficientmentioning
confidence: 99%
“…Blood rheology has been the subject of many studies found in the literature. Often, WBV measurements have been carried out using standard (shear) rheometers (cf Cowan et al [4]), implying that the flow is laminar and that the shear rate is well defined and solely dependent on the rotation rate (cf Agarwal et al [5]). Yamamoto et al [6] used a compact-sized falling needle rheometer on fresh blood samples to measure the relationship between the shear stress (τ) and shear rate (γ).…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices that can provide in vitro biological microenvironments [ 15 , 16 ] or physiological capillary vessel structures [ 17 ] have been extensively adopted to measure rheological properties [ 18 , 19 , 20 ]. Several rheological properties, including viscosity [ 21 , 22 , 23 , 24 , 25 ], viscoelasticity [ 26 ], aggregation (or sedimentation) [ 27 , 28 ], deformability [ 29 ], and hematocrit [ 25 , 30 , 31 ], have been obtained by manipulating blood flows in microfluidic environments [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%